Oncolytic viral kinetics mechanistic modeling of Talimogene Laherparepvec (T‐VEC) a first‐in‐class oncolytic viral therapy in patients with advanced melanoma - Malidi Ahamadi; Johannes Kast; Po‐Wei Chen; Xiaojun Huang; Sandeep Dutta; Vijay V. Upreti (Wiley, 2023)
Abstract Talimogene Laherparepvec (T‐VEC) is a first‐in‐class oncolytic virotherapy approved for the treatment of unresectable melanoma recurrent after initial surgery. Biodistribution data from a phase II study was used to develop a viral kinetic mechanistic model describing the interaction between cytokines such as granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), the immune system, and T‐VEC treatment. Our analysis found that (1) the viral infection rate has a great influence on T‐VEC treatment efficacy; (2) an increase in T‐VEC dose of 102 plaque‐forming units/ml 21 days and beyond after the initial dose of T‐VEC resulted in an ~12% increase in response; and (3) at the systemic level, the ratio of resting innate immune cells to the death rate of innate immune impact T‐VEC treatment efficacy. This analysis clarifies under which condition the immune system either assists in eliminating tumor cells or inhibits T‐VEC treatment efficacy, which is critical to both efficiently design future oncolytic agents and understand cancer development.